Circular slot antenna array printed on 3D textile substrate - Špůrek, Jan; Raida, Zbyněk; Láčík, Jaroslav; Mikulášek, Tomáš; Vélim, Jan; Prášek, Jan (International Society for Science and Engineering, o.s., 2017)
In the paper, design of an antenna array consisting of circular slots is presented. The array is expected to be integrated into the textile upholstery of a vehicle, therefore a 3D textile material is chosen as a substrate. Metallic layers are screen-printed by a silver paste. The array is fed by a textile integrated waveguide whose walls are sewed by a conductive thread. The array is optimized for the center frequency of band-group VI (8 GHz) of the UWB communication channels. The design is verified by measurements.